A Review on Cyber Security and Cyber Attacks - Fadhel Najem, Duaa; Muhajer Kareem, Suhad (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2025)
As technology has advanced, data protection has gotten more challenging. Information security now depends on cyber security. These days, protecting information is one of the biggest problems. Unquestionably, the Internet has created a new avenue for exploitation known as cybercrime because of the limitless amount of free websites. To combat these cybercrimes, both the public and business sectors are implementing a number of initiatives. Managing cyber security is a major challenge. In addition to presenting new trends and issues in the realm of cyber security, this research study focuses on upcoming technologies. It is anticipated that the thorough review study offered to scholars studying IT and cyber security will be beneficial. This analysis examines current advancements, difficulties, and new technology in the cybersecurity space. We concentrate on important ideas like cyber threats, and cyber threat intelligence. The relevant literature from 2020 to 2024 is evaluated using a systematic review methodology. This study aims to explore current trends, challenges, and future directions in cybersecurity and identify major cyber threats.